Adrenal lymphoma presenting as primary hypoadrenalism in the elderly. Issue 9 (11th September 2019) - Bhargava, Raghav; Dixon, Anthony
Abstract : Adrenal lymphoma causing primary hypoadrenalism in the elderly is a very rare finding. We describe a case of an 85-year-old man who was admitted to our hospital. He had a short history of hypotension and unresponsiveness. He was referred to the endocrine team, after a CT scan of his thorax abdomen and pelvis demonstrated significant enlargement of both his adrenal glands with associated lymphadenopathy. This scan was originally done to rule out an occult intra-abdominal malignancy. In addition, a tetracosactide (short Synacthen) test demonstrated adrenal insufficiency. This case demonstrates that adrenal lymphoma should be considered as an important differential when there is evidence of adrenal gland hyperplasia, lymphadenopathy and adrenal insufficiency.